PENGARUH RISIKO KREDIT TERHADAP KINERJA KEUANGAN BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020–2024 - Rizki Hidayatullah; Muhamad Teguh Suprayogi; Farah Margaretha Leon (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines the effect of credit risk on the financial performance of conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Financial performance is measured using Return on Assets (ROA), while credit risk is represented by Non-Performing Loans (NPL), Loan Loss Provisions (LLP), and Insider Lending (INSL). In addition, the Capital Adequacy Ratio (CAR) is included as an independent variable, while Firm Size serves as a control variable. This study employs a quantitative approach using secondary data obtained from the annual financial statements of listed banks. The sample consists of 27 conventional banks selected through purposive sampling, resulting in 135 firm-year observations. Panel data regression analysis was conducted using EViews software. The results indicate that NPL has a positive and significant effect on ROA at the 10% significance level, while LLP has a negative and significant effect on ROA. Meanwhile, Insider Lending and CAR do not have a significant effect on financial performance. Firm Size is found to have a positive and significant effect on ROA. These findings suggest that although credit quality and Loan Loss Provisioning remain important determinants of bank profitability, adequate capital levels and Insider Lending practices do not necessarily influence financial performance. The study highlights the importance of effective credit risk management, particularly in controlling Loan Loss Provisions, to maintain profitability in the Indonesian banking sector.